Waiting for the barbarians [videorecording (DVD)] - Rylance, Mark; Depp, Johnny; Pattinson, Robert, 1986-; Scacchi, Greta; Coetzee, J. M., 1940- (Samuel Goldwyn Films, 2020)
The Magistrate of an isolated frontier settlement on the border of an unnamed empire looks forward to an easy retirement until the arrival of Colonel Joll, whose task it is to report on the activities of the "barbarians" and the security situation on the border. Joll conducts a series of ruthless interrogations, which leads the Magistrate to question his loyalty to the empire.